Introduction to How Digital Resources Alter Design Landscape - Despina Potari; Giorgos Psycharis (Handbook of Digital Resources in Mathematics Education, 2023)
The main purpose of this section is to explore the design of and design with digital resources (DRs) for mathematics teaching and learning. Design of DRs involves teachers’ engagement in the process where DRs are the product of design. Design with DRs refers to cases where DRs facilitate the design-work offering an environment for teacher collaboration (e.g., communication platform) or an environment for designing tasks and lessons. The chapters of this section address both forms of design.